Comparative study on shrinkage & creep behaviour in self compacting connrete & normal vibrated concrete - Mohd Saifullah Bin Abd Nasir, Mohd Saifullah (2009)
This study however is limited to only one mix of SCC and one mix of normal vibrated concrete as a control. Effects of temperature and humidity are observed as well. Compressive strength development is determined at 3,7 and 28 days. The study is carried out using Modulus of Elasticity equipment for shrinkage and specially fabricated steel equipment is used to measure creep.